2020
DOI: 10.1055/a-1261-9605
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided radiofrequency ablation of pancreatic neuroendocrine tumors: a systematic review of the literature

Abstract: Background and study aims Surgery is the mainstay therapy for pancreatic neuroendocrine tumors (P-NETs), but it is associated with significant adverse events (AEs). In recent years, endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) has been described for treating P-NETs. We performed a systematic literature review aimed at exploring the feasibility, effectiveness, and safety of EUS-RFA in treatment of P-NETs. Methods The literature review was performed in PubMed/MEDLINE, EMBASE, and SCOP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
1
26
2
2
Order By: Relevance
“…A recent systematic review demonstrated that lesion size ≤18 mm had a very high positive predictive value of 97.1% predicting response to EUS-RFA of PNETs. [ 44 ] In our study, head/neck location of PNETs was associated with a positive predictor of clinical success after EUS-RFA, likely due to proximal location and relative ease of access leading to more complete ablation of lesions. However, we did not find a location to be a significant predictor after EUS-EA ablation, likely due to a smaller number of studies in EUS-EA group.…”
Section: Discussionmentioning
confidence: 71%
“…A recent systematic review demonstrated that lesion size ≤18 mm had a very high positive predictive value of 97.1% predicting response to EUS-RFA of PNETs. [ 44 ] In our study, head/neck location of PNETs was associated with a positive predictor of clinical success after EUS-RFA, likely due to proximal location and relative ease of access leading to more complete ablation of lesions. However, we did not find a location to be a significant predictor after EUS-EA ablation, likely due to a smaller number of studies in EUS-EA group.…”
Section: Discussionmentioning
confidence: 71%
“…The role of RFA has also been described for functional NETs[ 60 ]. In a recent meta-analysis, the role of RFA in pancreatic neuroendocrine tumors demonstrated an overall effectiveness of 96% without differences between functional and nonfunctional NETs[ 61 ].…”
Section: Interventional Eus In Pancreatic Cancermentioning
confidence: 99%
“…Radiologic complete response was achieved in 96.3% of patients (17 of 18) during a median of 8.7 months without clinically significant recurrence. In 2020, de Nucci et al [15] reported a prospective study on EUS-RFA in 10 patients with 11 NETs. At the 12-month follow-up, all lesions demonstrated complete disappearance with radiological normalization.…”
Section: Outcomes Of Eus-rfa In Benign Solid Pancreatic Tumormentioning
confidence: 99%